Taming our Wild Data: On Intercoder Reliability in Discourse Research - van Enschot, Renske; Spooren, Wilbert; van den Bosch, Antal; Burgers, Christian; Degand, Liesbeth; Evers-Vermeul, Jacqueline; Kunneman, Florian; Liebrecht, Christine; Linders, Yvette; Maes, Alfons (Dutch Journal of Applied Linguistics, 2024)
Many research questions in the field of applied linguistics are answered by manually analyzing data collections or corpora: collections of spoken, written and/or visual communicative messages. In this kind of quantitative content analysis, the coding of subjective language data often leads to disagreement among raters. In this paper, we discuss causes of and solutions to disagreement problems in the analysis of discourse. We discuss crucial factors determining the quality and outcome of corpus analyses, and focus on the sometimes tense relation between reliability and validity. We evaluate formal assessments of intercoder reliability. We suggest a number of ways to improve the intercoder reliability, such as the precise specification of the variables and their coding categories and carving up the coding process into smaller substeps. The paper ends with a reflection on challenges for future work in discourse analysis, with special attention to big data and multimodal discourse.